Photography in the planning of health interventions for the elderly - António Geraldo Manso Calha; Francisco José Lourenço Monteiro; Margarida Isabel Torcato Hilário
ABSTRACT Objective: To analyze potentialities of the use of photo-elicitation technique as a tool of access to the real needs of the beneficiaries of the intervention of health professionals. For this purpose, the aspects of their quality of life that they considered more relevant were identified with an elderly group. Method: It is a qualitative investigation in which the discourse of the elderly on the changes to their quality of life is encouraged through the use of photographic images. Results: Based on the data obtained, it was possible to identify the aspects of quality of life considered more relevant by the elderly, allowing, therefore, to sustain a later intervention adjusted to the needs and expectations of the elderly. Final considerations: The use of photo-elicitation allowed verifying its potentialities as a strategy to collect significant and relevant information for the planning of interventions in the Health area.